2018
DOI: 10.1111/mice.12347
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of Interdependent Urban Infrastructure Networks: Equilibrium after Failure Propagation and Cascading Impacts

Abstract: The functionality of modern cities relies heavily on interdependent infrastructure systems such as those for water, power, and transportation. Disruptions often propagate within and across physical infrastructure networks and result in catastrophic consequences. The reaction of communities to disasters (e.g., seeking alternative resource sources) may further transfer and aggravate the burden on surviving infrastructures, which may facilitate cascading secondary disruptions. Hence, a holistic analysis framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…However, it might not be directly translatable to the vulnerability measurement of a specific channel section. Besides, recent events demonstrated that cascading failure in interdependent infrastructure systems can lead to catastrophic consequences (Dong, Mostafizi, Wang, Gao, & Li, ; Dong, Wang, Gao, & Mostafavi, ; Dong, Wang, Mostafizi, & Song, ; Goldbeck, Angeloudis, & Ochieng, ; Lu et al., ). H&H models generate various inundation maps using rainfall information as the input.…”
Section: Introductionmentioning
confidence: 99%
“…However, it might not be directly translatable to the vulnerability measurement of a specific channel section. Besides, recent events demonstrated that cascading failure in interdependent infrastructure systems can lead to catastrophic consequences (Dong, Mostafizi, Wang, Gao, & Li, ; Dong, Wang, Gao, & Mostafavi, ; Dong, Wang, Mostafizi, & Song, ; Goldbeck, Angeloudis, & Ochieng, ; Lu et al., ). H&H models generate various inundation maps using rainfall information as the input.…”
Section: Introductionmentioning
confidence: 99%
“…The common modeling device by which the network flow pattern can be estimated is the traffic assignment under UE conditions. The notion of UE was initially proposed by Wardrop (), followed by intensive research in the field of traffic assignment modeling (Ziliaskopoulos et al., ; Meng and Wang, ; Bekhor et al., ; Unnikrishnan and Waller, ; Wen et al., ; Lu et al., ). Recently the UE traffic assignment considering EVs’ recharge needs—which incorporates vehicles’ distance constraints—has attracted increasing attention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Situational awareness about evolving and life‐threatening impacts of natural disasters like hurricanes, wildfires, and earthquakes is crucial for effective disaster response and recovery (Kryvasheyeu et al., ; Lu & Brelsford, ). A key component of a community is critical infrastructure systems, the damages and failures of which will make severe impacts on human systems (Kadri, Birregah, & Châtelet, ; Kim & Hastak, ) and physical environment (Lu et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…A key component of a community is critical infrastructure systems, the damages and failures of which will make severe impacts on human systems (Kadri, Birregah, & Châtelet, 2014;Kim & Hastak, 2018) and physical environment (Lu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%